Labor Market Effects of a Minimum Wage: Evidence from Ecuadorian Monthly Administrative Data - Jaerim Choi; Ivan Rivadeneyra; Kenia Ramirez (Center for Economic Studies and Ifo Institute (CESifo), 2021)
When Ecuador raised its monthly Unified Minimum Wage from 170 to 200 in 2008, it affected 35 percent of all private sector workers. We use this unexpected minimum wage hike under former president Rafael Correa to assess the labor market impacts of the minimum wage. We use an administrative dataset that covers all formal sector workers by month. Adopting a differences-in-differences approach at the firm level, we find that the minimum wage hike led to a decrease in labor demand in affected firms by 0.5 percent after one month and by 2.5 percent after four months. The decrease in labor demand resulted from both an increase in job separations and a slowdown in hiring. At the worker level, we find that the minimum wage hike led to a 2.2 percentage point decline in the probability of remaining employed after one month, and the treatment effect rose to 3.9 percentage points after four months. Last, we estimate the effects of the minimum wage hike on wage changes by wage bin throughout the monthly wage distribution. We find that, after one month, wages increased by 17 to 37 percent for workers who were being paid less than 200 and also uncover wage spillover effects up to the 77th percentile of the wage distribution.
Keywords: J23; J38; J88; 330; minimum wage; job separations; new hires; worker flows; wage distribution; wage spillover effects; differences-in-differences; employment; Ecuador